The digital transformation of logistics : demystifying impacts of the fourth industrial revolution - Sullivan, Mac; Kern, Johannes (Writer on logistics) (IEEE Press series on technology management, innovation, and leadership, 2021)
"This book covers the latest trends in the changing landscape of international logistics in terms of technological developments and the effects of these changes. The authors introduce relevant technologies and related concepts and provide their expert opinion on the future impact of these technologies on the logistics field and the professionals working in this space. The book analyzes artificial intelligence, robotic process automation, Blockchain, Internet of Things (IoT), Enterprise Resource Planning systems (ERPs), Digital Marketplaces and Digital Networks as part of Industry 4.0. Real experiences in dealing with the effects of technology on jobs in the logistics industry are translated into learning points. This book equips the reader with the fundamentals to hold a conversation with their employers, customers, investors, and suppliers about how they can prepare for the disruptive forces shaping the industry"--